Engineering your future : the professional practice of engineering - Walesh, Stuart G. (John Wiley & Sons, 2012)
Technical competency, the "hard side" of engineering and other technical professions, is necessary but not sufficient for success in business. Young engineers must also develop nontechnical or "soft-side" competencies like communication, marketing, ethics, business accounting, and law and management in order to fully realize their potential in the workplace. This updated edition of Engineering Your Future is the go-to resource on the nontechnical aspects of professional practice for engineering students and young technical professionals alike. The content is explicitly linked to current efforts in the reform of engineering education including ABET's Engineering Criteria 2000, ASCE's Body of Knowledge, and those being undertaken by AAEE, AIChE and ASME. The book treats essential nontechnical topics you'll encounter in your career, like self-management, interpersonal relationships, teamwork, project and total quality management, design, construction, manufacturing, engineering economics, organizational structures, business accounting, and much more. Features new to this revised edition include: A stronger emphasis on management and leadership. A focus on personal growth and developing relationships. Expanded treatment of project management. Coverage of how to develop a quality culture and ways to encourage creative and innovative thinking. A discussion of how the results of design, the root of engineering, come to fruition in constructing and manufacturing, the fruit of engineering. New information on accounting principles that can be used in your career-long financial planning. An in-depth treatment of how engineering students and young practitioners can and should anticipate, participate in, and ultimately effect change. If you're a student or young practitioner starting your engineering career, Engineering Your Future is essential reading